A Study of the Level of Applying Creative Accounting in Vietnamese Companies - Lien, Nguyen Thi Huong; Ngan, Dao Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
Creative accounting has been an interesting research topic because it relates to manupulations of actual accounting figures to the ones desired by the management by taking advantage of the existing accounting rules or ignoring them. Based on literature review and survey on companies of different sectors in Hanoi, this research summarizes popular techniques and motivations of using creative accounting, and evaluates the trend and the level of applying creative accounting in Vietnamese companies. The research results show an increasing trend of using creative accounting in Vietnam, and the level of applying creative accounting depends on the size and the type of companies, and motivations of using creative accounting are mainly for the purpose of tax benefit optimization, business value added and budget achievement. Keywords Creative accounting techniques, application trend, creative accounting motivations, level of application. References [1] Yadav, B., “Creative accounting: A Literature Review”, The SIJ Transactions on Industrial, Financial & Business Management (IFBM), 1 (2013) 5. [2] Naser, K., “A Note on the Use of Creative Accounting”, British Accounting Review, 24 (1992) 2, 111-118. [3] Hussein, H.N., Kasim, N., Aurumugam V.,“A Review of Creative Accounting Practices and its Area, Technique and Ways of Prevention”, International Journal of Science and Research (IJSR), 4 (2013) 10. [4] Palepu, K.G., Walker, R.G., Healy, P.M., Williston, J.R., Business Analysis & Valuation Using Financial Statements, Thomson South-Weston, 2007. [5] Schilit, H.M., Perler, J., Financial Shenanigans, Mc GrawHill, 2010. [6] Minh An, “Liên tục chênh lệch sau kiểm toán: Doanh nghiệp đang vẽ gì”, Cổng Thông tin và Dữ liệu Tài chính - Chứng khoán Việt Nam, truy cập ngày 20/6/2017, https://vietstock.vn/2015/10/lien-tuc-chenh-lech-sau-kiem-toan-doanh-nghiep-dang-ve-gi-737-441594.htm , 2015.